The Men's Safer Sex Trial: A feasibility randomised controlled trial of an interactive digital intervention to increase condom use in men. (November 2016) - Bailey, Julia V; Webster, Rosie; Griffin, Mark; Freemantle, Nick; Hunter, Rachael; Rait, Greta; Estcourt, Claudia; Anderson, Jane; Gerressu, Makeda; Stephenson, Judith; Michie, Susan; Murray, Elizabeth
Objectives: We aimed to determine the feasibility of an online randomised controlled trial (RCT) of the Men's Safer Sex website, measuring condom use and sexually transmitted infection (STI). Methods: For this study 159 men aged ≥16 with female sexual partners and recent condomless sex or suspected STI were recruited from three UK sexual health clinics. Participants were randomised to the intervention website plus usual clinic care ( n = 84), or usual clinic care only ( n = 75). Online outcome data were solicited at 3, 6, and 12 months. Results: Men were enrolled via tablet computers in clinic waiting rooms. Software errors and clinic Wi-Fi access presented significant challenges, and online questionnaire response rates were poor (36% at 3 months with a £10 voucher; 50% at 12 months with £30). Clinical records (for STI diagnoses) were located for 94% of participants. Some 37% of the intervention group did not see the intervention website ( n = 31/84), and (as expected) there was no detectable difference in condomless sex with female partners (IRR = 1.01, 95% CI 0.52 to 1.96). New acute STI diagnoses were recorded for 8.8% (7/80) of the intervention group, and 13.0% (9/69) of the control group over 12 months (IRR = 0.75, 95% CI 0.29 to 1.90). Conclusion: It is likely to be feasible to conduct a future large-scale RCT to assess the impact of an online intervention using clinic STI diagnoses as a primary outcome. However, practical and technical challenges need to be addressed before the potential of digital media interventions can be realised in sexual health settings. Trial registration number: ISRCTN18649610